Žodžių tvarka ir baltų kalbų sakinio tipo rekonstrukcija - Ambrazas, Vytautas (Baltistica, 1982)
Word order and reconstruction of Baltic sentence typeThe article deals with mutual relations between word order patterns in Lithuanian and Lettish and points out their importance for the reconstruction of earlier Baltic sentence structure. Statistic evidence reveals the greater frequency of the OV pattern (from 51% to 75%) in dialects and folklore, especially in the older recordings, in comparison with standard language. The ancient character of this pattern is corroborated by the order of components in nominal compounds such as Lith. kraugerỹs “blood-sucker”, varkalỹs (Lett. varkalis) “copper-smith”, bìtkopis (Lett, biškuopis) “honey-taker”. The (S)OV order of the major sentence constituents is in accordance with the majority of phrase constituent patterns in which the modifier (operator) precedes the modified (operandum): AdjNom, PronNom, NumNom, GenNom; AdvV, Adv'Adv, etc. Other patterns with the preceding modifier can be reconstructed for the earlier history of the Baltic languages. The ancient use of postpositions reflect the locatives with -pi< *pie, *en, -na (Lith. Namóp(i), laukè, laukúosna), adverbs Lith. kodė̃l, todė̃l, kodrin, todrin, Lett, kāpēc tāpēc etc. The standard of comparison precedes adjective in the majority of gnomic expressions, proverbs and riddles of Lithuanian folklore and especially in such periphrastic comparatives as Lith. visų̃ geràsis (geriáusias), Lett. vislabâks “best of all”. Nominal phrases with definite adjectives, f. i. Lith. gerasis (
Keywords: word order; syntaxis; baltic sentence type reconstruction